Calibration of insulin pumps based on discrete doses at given cycle times - Bissig, Hugo (2023)
One application in the medical treatment at very small flow rates is the usage of an Insulin pump that delivers doses of insulin at constant cycle times for a specific basal rate as quasi-continuous insulin delivery, which is an important cornerstone in diabetes management. The calibration of these basal rates are performed by either gravimetric or optical methods, which have been developed within the European Metrology Program for Innovation and Research (EMPIR) Joint Research Project (JRP) 18HLT08 Metrology for drug delivery II (MeDDII). These measurement techniques are described in this paper, and an improved approach of the analytical procedure given in the standard IEC 60601-2-24:2012 for determining the discrete doses and the corresponding basal rates is discussed in detail. These improvements allow detailed follow up of dose cycle time and delivered doses as a function of time to identify some artefacts of the measurement method or malfunctioning of the insulin pump. Moreover, the calibration results of different basal rates and bolus deliveries for the gravimetric and the optical methods are also presented. Some analysis issues that should be addressed to prevent misinterpreting of the calibration results are discussed. One of the main issues is the average over a period of time which is an integer multiple of the cycle time to determine the basal rate with the analytical methods described in this paper.